Cutaneous adverse reactions after COVID‐19 vaccines in a cohort of 2740 Italian subjects: An observational study. Issue 6 (13th October 2021) - Grieco, Teresa; Maddalena, Patrizia; Sernicola, Alvise; Muharremi, Rovena; Basili, Stefania; Alvaro, Domenico; Cangemi, Roberto; Rossi, Alfredo; Pellacani, Giovanni
Abstract: An in‐depth characterization of the incidence, morphology, and onset of COVID‐19‐vaccines cutaneous adverse reactions is currently lacking. The existing literature on COVID‐19 vaccination‐related cutaneous adverse reactions largely focused on messenger RNA vaccines and mainly included type 1 hypersensitivity reactions, such as urticaria and angioedema. Other cutaneous manifestations are still poorly characterized and have been classified as delayed hypersensitivity rash. Our prospective observational study on a sample of 2740 subjects who underwent the COVID‐19 vaccination aimed at defining the prevalence of cutaneous adverse reactions and at identifying their timing of onset and their correlation with the administered dose. Vaccine‐related cutaneous adverse reactions occurred in 50 subjects. Patients were asked to complete a questionnaire on the type of COVID‐19 vaccine received, the time of onset of cutaneous reactions, and the dates of administration. Out of 2740 individuals who received the COVID‐19 vaccination, 50 were diagnosed with cutaneous adverse reactions to vaccine, after the first dose in 28 patients, after the second in 20, and after both in two. We reported localized injection site erythema in 12 patients and generalized cutaneous reactions in 38 patients. Our study shows that cutaneous adverse reactions to COVID‐19 vaccination are not common and most often occur after the first dose, recurring infrequently after the second dose. These reactions are usually easily manageable and, even in severe generalized cases, oral antihistamines and corticosteroids were sufficient for resolution. Therefore, except for immediate hypersensitivity reactions, cutaneous adverse reactions do not represent a contraindication to the completion of the vaccination cycle.